Mapping the implementation and challenges of clinical services for psychosis prevention in England - Estradé, Andrés; Spencer, Tom John; De Micheli, Andrea; Murguia-Asensio, Silvia; Provenzani, Umberto; McGuire, Philip; Fusar-Poli, Paolo (Frontiers in Psychiatry, 2023)
Introduction: Indicated primary prevention of psychosis is recommended by NICE clinical guidelines, but implementation research on Clinical High Risk for Psychosis (CHR-P) services is limited. Methods: Electronic audit of CHR-P services in England, conducted between June-September 2021, addressing core implementation domains: service configuration, detection of at-risk individuals, prognostic assessment, clinical care, clinical research, and implementation challenges, complemented by comparative analyses across service model. Descriptive statistics, Fisher’s exact test and Mann-Whitney U tests were employed. Results: 24 CHR-P clinical services (19 cities) were included. Most (83.3%) services were integrated within other mental health services; only 16.7% were standalone. Across 21 services, total yearly caseload of CHR-P individuals was 693 (average: 33; range: 4-115). Most services (56.5%) accepted individuals aged 14-35; the majority (95.7%) utilised the Comprehensive Assessment of At Risk Mental States (CAARMS). About 65% of services reported some provision of NICE-compliant interventions encompassing monitoring of mental state, cognitive-behavioural therapy (CBT), and family interventions. However, only 66.5% and 4.9% of CHR-P individuals actually received CBT and family interventions, respectively. Core implementation challenges included: recruitment of specialised professionals, lack of dedicated budget, and unmet training needs. Standalone services reported fewer implementation challenges, had larger caseloads (p=0.047) and were more likely to engage with clinical research (p=0.037) than integrated services. Discussion: While implementation of CHR-P services is observed in several parts of England, only standalone teams appear successful at detection of at-risk individuals. Compliance with NICE-prescribed interventions is limited across CHR-P services and unmet needs emerge for national training and investments.